What to Examine in Youth Climbing Athletes: Yearly Examination of the German Climbing Team and its Consequences - Schöffl, Isabelle; Lutter, Christoph; Schöffl, Volker (Sportverletzung · Sportschaden, 2019)
Objective This article presents the results of the yearly medical examination performed on all our national climbing athletes in 2016 and 2017.Methods Our yearly athlete examination follows the Olympic guidelines and those of the Medical Commission of the International Federation of Sport Climbing. It consists of echocardiography, spiroergometry, a general blood examination, body fat measurement as well as a paediatric and orthopaedic clinical examination. In addition, a yearly ultrasound examination is performed on the fingers to detect pathologies and measure the width of the growth plates. The years 2016/2017 were evaluated.Results Team examinations were undertaken in 17 girls and 23 boys. The mean age was 17.5 years (18.3 years for the boys and 17.4 years for the girls). They had been climbing for 10.9 years on average (the boys for 11.3 and the girls for 10.3 years). Typical findings were susceptibility to infection, musculoskeletal injuries and, in one case, severe headaches. 36 % of our athletes had to take a break from climbing due to injury or illness. Most of these breaks were due to infections (7 in total), most of them minor inspiratory or gastrointestinal. One athlete suffered from severe pneumonia during a World Cup in Japan. The other pauses were due to finger injuries (2), foot injuries (2), and injuries to the shoulder and biceps (2).Conclusion The yearly team examination plays an important role in early injury detection. It helps to establish a relationship based on trust, encouraging athletes to approach the team physician openly with questions or concerns.
Keywords: rock climbing; sport climbing; finger injuries; team exam; sports medical exam; national team